Una seconda opportunità per le cose. Circuito del dono e processi di mercificazione in un emporio dello scambio e del baratto - Viola Lucrezia Giuliani (Archivio Antropologico Mediterraneo)
The article focuses on the analysis of the methods of acquisition and supply of objects in an emporium of exchange and barter, the “Senza Monete”, located in Orvieto, in the province of Terni. Through semi-structured interviews and participant observation, I would like to put forward some reflections on consumption and exchange by analyzing the ways of circulation of goods within this peculiar association reality. The results that emerged during the research highlight gift-related dynamics, which sometimes go beyond the barter principle that regulates most exchanges within the Emporium. The interviews addressed to the members have also shown an interesting heterogeneity within the process from approaching to consumption, demonstrating how a strong, sometimes contradictory, critic towards consumerism impacts most of their choices, when these are not dictated by financial needs. The “Senza Monete” presents itself as a paradigmatic case, a place that offers a second chance to objects thanks to the time donated voluntarily by a team of people who is trying to cope with an increasingly felt social and economic crisis.